Understanding pulsar magnetospheres with the SKA - Karastergiou, A.; Johnston, S.; Andersson, N.; Breton, R.; Brook, P.; Gwinn, C.; Lewandowska, N.; Keane, E.; Kramer, M.; Macquart, Jean-Pierre; Serylak, M.; Shannon, R.; et al. (SPIE - Internatioal Society for Optocal Engineering, 2014)
The SKA will discover tens of thousands of pulsars and provide unprecedented data quality on these, as well as the currently known population, due to its unrivalled sensitivity. Pulsars are known to be variable on numerous timescales: from nanoseconds to decades, corresponding to events, likely associated with the emission process itself through to discrete stable magnetospheric states. Timescales in between show phenomena such as pulse-to-pulse variations, sub-pulse drifting and nulling in operation, in addition to the relevant orbital, cooling and magnetic field decay timescales. The SKA will allow us to study these effects with higher fidelity than ever before. Moreover, it will be possible to perform these studies down to the individual pulse level for a large sample of millisecond pulsars. With their significantly different magnetic field strength and magnetospheric extent, this will provide important clues to the magnetospheric physics. Polarization profiles of a large number of pulsars, and their evolution over a broad frequency range, will enable us to perform measurements, with unprecedented detail, of the geometry of the emission regions of these systems. In addition to studying the plethora of new sources, we will perform intense targeted studies of already known objects. For example, with the SKA we will get a unique view of the magnetospheres of the two stars in the Double Pulsar System, down to the precision of a single rotation period, over a wide range of frequencies with full polarization information. We will be able to map the magnetospheres of selected sources by performing high sensitivity observations from 50 MHz all the way through to gamma-rays. Furthermore, using scintillation imaging techniques, we will be able to actually resolve pulsar magnetospheric features. With the good sample of radio-emitting magnetars from SKA, we will be able to compare, and identify any magnetospheric differences, between these and the standard pulsar population. As well as finally settling the questions about the pulsar emission mechanism and magnetospheric structure once and for all, we can use this understanding to improve pulsars' usefulness as astrophysical tools.